2022
DOI: 10.1177/02676591221080653
|View full text |Cite
|
Sign up to set email alerts
|

One-shot cardioplegia for minimally invasive mitral valve repair-a comparison of del Nido and Bretschneider Histidine-Tryptophan-Ketoglutarate solutions

Abstract: Background Minimally invasive procedures are demanding in terms of cardioprotection. In many leading centres Bretschneider HTK solution is used for mitral valve surgery. The study was designed to provide comparison of the del Nido and Bretschneider HTK protocol. Methods Patients who underwent minimally invasive mitral valve repair for primary mitral regurgitation and received single delivery of either del Nido (Group 1) or Bretschneider HTK cardioplegia (Group 2) were matched on basis of age, gender and length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…23 There is limited literature focusing on outcomes of patients who underwent minimally invasive mitral surgery using del Nido cardioplegia. These studies provided a direct comparison between patients who had del Nido cardioplegia versus HTK or St Thomas solutions [12][13][14] and showed, by including operations with a median crossclamp time range of [54-76] minutes, equivalent results in terms of early mortality and morbidity and lower release of myocardial enzymes after del Nido cardioplegia. 12 Our data showed that there was no difference in postoperative peak Troponin I HS and CK-MB between the two groups both in the overall matched populations and in patients who underwent isolated mitral surgery.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…23 There is limited literature focusing on outcomes of patients who underwent minimally invasive mitral surgery using del Nido cardioplegia. These studies provided a direct comparison between patients who had del Nido cardioplegia versus HTK or St Thomas solutions [12][13][14] and showed, by including operations with a median crossclamp time range of [54-76] minutes, equivalent results in terms of early mortality and morbidity and lower release of myocardial enzymes after del Nido cardioplegia. 12 Our data showed that there was no difference in postoperative peak Troponin I HS and CK-MB between the two groups both in the overall matched populations and in patients who underwent isolated mitral surgery.…”
Section: Commentmentioning
confidence: 99%
“…[9][10][11] Few data are available regarding its use in minimally invasive mitral valve surgery and a limited number of studies have compared del Nido and HTK solutions. [12][13][14] The aim of our study was to review and compare the early clinical outcomes associated with the use of del Nido and HTK cardioplegia solutions in the setting of right mini-thoracotomy mitral valve surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation